SIKAP DAN KEPUASAN KONSUMEN KOPI BUBUK GUNUNG SEKINCAU DI KECAMATAN SEKINCAU KABUPATEN LAMPUNG BARAT - Tifany Oktaviana; Dwi Haryono; Erlina Rufaidah (Lampung University, 2023)
This study aims to analyze consumer characteristics, consumer attitudes, and levels of consumer satisfaction on Gunung Sekincau ground coffee products. This study used a survey method through a qualitative descriptive approach with 50 samples. The analytical method uses the Fishbein Multi-attribute Model, Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results showed that most of the consumers of Gunung Sekincau ground coffee were male aged 24-30 years, with more than 3 family members, working as private employees with a monthly income of more than IDR3,000,000. The results of the study using Fishbein attribute analysis show that the taste is the most important attribute for consumers. Consumer attitude towards Gunung Sekincau ground coffee is 94.5% and in the fairly good category. The level of consumer satisfaction on Gunung Sekincau ground coffee is 81.33% and included in the very satisfied category. The price attribute belonging to quadrant I is an attribute that is still considered important by consumers, but its implementation is still considered low. Quadrant II, namely maintaining achievement, shows the level of importance that is considered high by consumers in their performance is also high, which belongs to this quadrant are the attributes of taste, aroma, and texture. Quadrant III shows the level of consumer interest that is still lacking and in its implementation by producers that is still lacking, the attributes in this quadrant are considered by consumers to be unimportant and ignored, the attributes included in this quadrant is location attribute. Quadrant IV contains attributes that are considered excessive by consumers with a low level of importance and in practice by producers considered by consumers to be quite high, the attributes included in this quadrant is packaging attribute.